Cloud Point Extraction, Preconcentration and Spectrophotometric Determination of Co (II) and Cu (II) using 15-Crown-5. - Yussra O.Mussa1, Azhar A. Ghali2, Ashwaq S.Hussei1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the current study, a cloud point extraction (CPE) with UV-vis spectrometry for detection of Cu (II) and Co (II) ions with 15-crown-5 as a chelating agent was developed to be more selective and sensitive. The CPE method is improving the analytical signal and permits the preconcentration of metals ions. After phase separation induced by change temperature to become higher more than the temperature of the cloud, the point is performed with centrifugation. The Co (II) and Cu (II) ions are determined in the enriched phase by UV-vis spectrometry. Several factors affecting the extraction efficiency were optimized, e.x. pH, the concentration of the chelating agent, non-ionic surfactant concentrations, and cloud point temperature. Under optimum conditions, a linear calibration graph in the range of 0.5-5 ?g mL-1 of Co (II) in the initial solution with r2 = 0.9994 (n=8) and 0.2–7?g of Cu(II) in the initial solution (mL-1) with r2 = 0.9991 (n=8) were obtained. Detection limits of 0.4and 0.1?g are for Co(II) and Cu(II) along with preconcentration factors (66 and 50) for these ions, respectively. The method was used for detection of Co(II) and Cu(II) in some food samples.